Timing, size and nitrogen concentration of faecal and urinary excretions in cattle, sheep and goats: An they be exploited for better manuring of cropland? - Schlecht, Eva; Fernández Rivera, S.; Hiernaux, Pierre H.Y. (Margraf Verlag, 1998)
The influence of forage type, feed allowance and watering time on faeces and urine excretion by cattle, sheep and goats was studied. Higher amounts of nitrogen (N) were excreted during the day than during the night. The occurrence of defaecation and urination was highest at the time of getting up and watering. In general, feed quality did not influence the amounts of faeces excreted, but increased urine-N excretion was observed with diets high in N content. The results suggest that herd management practices such as keeping the animals in corralled fields for about 30 minutes after getting up, and spreading litter near watering points, may allow to better capture manure and N for improving soil fertility.